2021
DOI: 10.12659/msm.932227
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Mortality of Sepsis in Intensive Care Units in Prefecture-Level Cities in Sichuan, China: A Prospective Multicenter Study

Abstract: Background Studies on the epidemiology of sepsis in intensive care units (ICUs) of prefecture-level hospitals in China are rare. This study aimed to investigate the epidemiological characteristics and mortality risk factors of sepsis in ICUs of tertiary hospitals in Sichuan, China. Material/Methods In this prospective, multicenter, observational study, patients admitted to the ICU of 7 tertiary hospitals in Sichuan (China) between October 10, 2017 and January 9, 2018 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Eight studies were published in English-language journals, while one study was in a Chinese-language journal. Of the nine studies, four ( 17 , 20 , 21 , 25 ) were conducted in hospital-wide, and five ( 18 , 19 , 22 24 ) were conducted in ICUs. In addition, four ( 17 , 20 , 21 , 25 ) studies were retrospective in design, four ( 18 , 19 , 22 , 24 ) were prospective, and one ( 23 ) was a cross-section survey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were published in English-language journals, while one study was in a Chinese-language journal. Of the nine studies, four ( 17 , 20 , 21 , 25 ) were conducted in hospital-wide, and five ( 18 , 19 , 22 24 ) were conducted in ICUs. In addition, four ( 17 , 20 , 21 , 25 ) studies were retrospective in design, four ( 18 , 19 , 22 , 24 ) were prospective, and one ( 23 ) was a cross-section survey.…”
Section: Resultsmentioning
confidence: 99%
“…Of the nine studies, four ( 17 , 20 , 21 , 25 ) were conducted in hospital-wide, and five ( 18 , 19 , 22 24 ) were conducted in ICUs. In addition, four ( 17 , 20 , 21 , 25 ) studies were retrospective in design, four ( 18 , 19 , 22 , 24 ) were prospective, and one ( 23 ) was a cross-section survey. The mean age of patients ranged from 36.8 years to 81 years.…”
Section: Resultsmentioning
confidence: 99%
“…Sepsis is symbolized by the systemic inflammatory response and multi‐organ failure; globally, there are about 49 million sepsis patients each year, of which 11 million patients die from sepsis 1 , 2 , 3 . In China, sepsis is also a prevalent infectious disease; it has been reported that among every 100 patients in the intensive care unit, there are 21 sepsis cases, whose mortality rate within 90 days has reached nearly 36% 4 , 5 . Apart from these, complications contributed by sepsis, including acute kidney injury (AKI), acute lung injury (ALI), disseminated intravascular coagulation, etc., are crucial causes of poor prognosis in sepsis patients 6 , 7 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In China, sepsis is also a prevalent infectious disease; it has been reported that among every 100 patients in the intensive care unit, there are 21 sepsis cases, whose mortality rate within 90 days has reached nearly 36% 4,5 . Apart from these, complications contributed by sepsis, including acute kidney injury (AKI), acute lung injury (ALI), disseminated intravascular coagulation, etc., are crucial causes of poor prognosis in sepsis patients [6][7][8][9] .…”
mentioning
confidence: 99%
“…In 2021, a study from Sichuan province reported that the current situation of sepsis treatment in western China. The mortality rate of sepsis patients was as high as 57.5% 5 , and the per capita hospitalization cost reached 11,390 dollars. Thus, sepsis was a global public health problem, killing more than 5 million people worldwide every year, which was a major economic burden for patients and society.…”
Section: Introductionmentioning
confidence: 99%